Systematic Review on International Practices in Controlling Waterpipe Tobacco Smoking - Tee, G.H.; Hairi, N.N.; Nordin, F.; Choo, W.Y.; Chan, Y.Y.; Kaur, G.; Veerasingam, P.D.; Bulgiba, A. (Asian Pacific Organization for Cancer Prevention, 2015)
Background: Waterpipe tobacco smoking has becoming popular especially among young people worldwide. Smokers are attracted by its sweeter, smoother smoke, social ambience and the misconception of reduced harm. The objective of this study was to systematically review the effects of waterpipe tobacco policies and practices in reducing its prevalence. Materials and Methods: A systematic review was conducted electronically using the PubMed, OVID, Science Direct, Proquest and Embase databases. All possible studies from 1980 to 2013 were initially screened based on titles and abstracts. The selected articles were subjected to data extraction and quality rating. Results: Three studies met the inclusion criteria and were eligible for this review. Almost all of the waterpipe tobacco products and its accessories did not comply with the regulations on health warning labelling practices as stipulated under Article 11 of WHO FCTC. In addition, the grisly new warning labels for cigarettes introduced by Food and Drug Administration did not affect hookah tobacco smoking generally. Indoor air quality in smoking lounges was found to be poor and some hookah lounges were operated without smoke shop certification. Conclusions: Our findings revealed the availability of minimal information on the practices in controlling waterpipe smoking in reducing its prevalence. The lack of comprehensive legislations or practices in controlling waterpipe smoking warrants further research and policy initiatives to curb this burgeoning global epidemic, especially among the vulnerable younger population.